A performance analysis for MHD power cycles operating at maximum power density - Sahin, B; Kodal, A; Yavuz, H (IOP PUBLISHING LTD, 1996)
An analysis of the thermal efficiency of a magnetohydrodynamic (MHD) power cycle at maximum power density for a constant velocity type MHD generator has been carried out. The irreversibilities at the compressor and the MHD generator are taken into account. The results obtained from power density analysis were compared with those of maximum power analysis. It is shown that by using the power density criteria the MHD cycle efficiency can be increased effectively.
Keywords: Physics